2013
DOI: 10.4236/ajps.2013.43071
|View full text |Cite
|
Sign up to set email alerts
|

AACA Element Negatively Regulates Expression of Protein Phosphatase 2C (<i>PP2C</i>) like Promoter in <i>Arabidopsis thaliana</i>

Abstract: Genome wide analysis of Arabidopsis thaliana reveals a unique genetic arrangement of ACGT motif in the protein phosphatase 2C (PP2C) like promoter (accession number AT5G59220). In the present study, full length, 900 base pair, 500 base pair, 400 base pair and NRM deletion variants of PP2C like promoter were constructed to investigate the activity of PP2C like promoter in the presence of inducers like abscisic acid, jasmonic acid and salicylic acid. The PP2C promoter has three ACGT elements in close vicinity. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…It has been reported that Skn-1 motif in the promoter upregulates carotenogenic gene expression during flower development in Gentiana lutea (Zhu et al 2014). In A. thaliana, AACA is a positive regulatory element in the endosperm (PP2C promoter) and functions as a negative regulatory element in other tissues (Bhalothia et al 2013). The CCAAT box elements interact with transcription factor NF-Y for efficient transcription (Zanotto et al 2007).…”
Section: Identification Of Trapped Promoter and T-dna Localizationmentioning
confidence: 97%
“…It has been reported that Skn-1 motif in the promoter upregulates carotenogenic gene expression during flower development in Gentiana lutea (Zhu et al 2014). In A. thaliana, AACA is a positive regulatory element in the endosperm (PP2C promoter) and functions as a negative regulatory element in other tissues (Bhalothia et al 2013). The CCAAT box elements interact with transcription factor NF-Y for efficient transcription (Zanotto et al 2007).…”
Section: Identification Of Trapped Promoter and T-dna Localizationmentioning
confidence: 97%
“…Our work in the protein phosphatase 2C (PP2C) like promoter of Arabidopsis thaliana revealed that AACA element negatively regulated the expression of the above promoter, even in the presence of inducers [5].…”
Section: Short Commentarymentioning
confidence: 99%
“…The optimization of genetic transformation of Artemisia species will pave way to engineer a metabolic pathway for in-vivo enhanced production of the compound of our interest. Various genetic transformation methods are available, but most frequently BBiolistic method ( Rech et al 2008;Bhalothia et al 2013) and BAgrobacteriummediated^ (Upadhyay et al 2013;Elfahmi and Chahyadi, 2014) transformation are used. Agrobacterium-mediated genetic transformation is a cost effective and easier method for transformation of plants.…”
Section: Introductionmentioning
confidence: 99%